2011
DOI: 10.1111/j.1365-2842.2011.02241.x
|View full text |Cite
|
Sign up to set email alerts
|

Response shift in oral health‐related quality of life measurement in patients with partial edentulism

Abstract: The purposes of this study were to determine whether a response shift was observable after partial denture treatment and to identify the predictors that influenced the response shift magnitude and direction. A total of 173 consecutive patients with no more than eight missing teeth who received implant-supported, fixed or removable partial dentures at Okayama University Dental Hospital were asked to complete a full-version Oral Health-Related Quality of Life (OHRQoL) questionnaire before (pre-test) and after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…Studies have also shown that simple comparison between before and after treatment score might show paradoxical findings because of variations in patient's internal standards of quality of life (Kimura et al 2012;Reissmann et al 2012). Such response shifts are considered crucial component in treatment outcome, as it might also affect the scoring pattern observed in our study over time.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies have also shown that simple comparison between before and after treatment score might show paradoxical findings because of variations in patient's internal standards of quality of life (Kimura et al 2012;Reissmann et al 2012). Such response shifts are considered crucial component in treatment outcome, as it might also affect the scoring pattern observed in our study over time.…”
Section: Discussionmentioning
confidence: 76%
“…Studies have also shown that simple comparison between before and after treatment score might show paradoxical findings because of variations in patient's internal standards of quality of life (Kimura et al. ; Reissmann et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Kimura et al found younger patients treated with RPD have less OHRQoL. Such outcome could be attributed to higher social demand and self-concerns with aesthetics and oral function in comparison with older patients (18). On the other hand, older patients are more experienced to function with missing teeth (19).…”
Section: O R a L H E A L T H O F D E N T U R E W E A R E R S 45mentioning
confidence: 99%
“…; Kimura et al. ). OHRQoL is an effective and widely used instrument to measure the impact of treatment from the patients' point of view.…”
mentioning
confidence: 98%